[Imaging cervical myelo- and radiculopathy] - Roth, C; Papanagiotou, P; Krick, C; Reith, W; Grunwald, I (2006)
PURPOSE: This article gives an overview of the diagnostic possibilities available in the diagnosis of cervical myelo- and radiculopathy. We compared conventional myelography, CTM, and MRI. MATERIAL AND METHODS: Twenty-five patients with clinical evidence of cervical myelo- or radiculopathy were included. Sagittal and transverse T1-weighted (T1w) TSE and T2-weighted (T2w) TSE sequences were compared with myelography and CTM. Statistical analysis was performed using Wilcoxon's -test. RESULTS: Disc herniation could be depicted in CTM as well as in MRI. The extent of herniation did not differ between CTM and T1w. The extent of herniation seemed higher on T2w than on T1w (p <0.001). Foraminal encroachment was easier to diagnose in CTM. When regarding transverse T1w and T2w images simultaneously, a missing root in MRI corresponded to a missing root in CTM and conventional myelography and vice versa. Our data demonstrated the relative inability of MRI to determine whether the compression is by soft tissue or bony structures. CONCLUSION: The present study proposes that MRI, when available, should be the imaging method of first choice in patients with suspected radiculo- and myelopathy.